Barriers and incentives to reporting medication errors and near misses in a university hospital: perception of doctors, nurses and pharmacists - Ferreira Fernandes Machado, Juliana; Beisl Noblat, Antonio Carlos; de Araújo Costa Beisl Noblat, Lúcia (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2024)
Background: Medication errors produce substantial damage to the health of patients and institutions, though they are often under-reported. Objectives: The goal of this study is to understand the barriers and incentives to the reporting of medication errors and near misses according to the perception of doctors, nurses and pharmacists, and to explore the understanding of the institution’s medication error reporting systems. Methods: It is a qualitative study in which individual semi-structured interviews were carried out. The interviews were transcribed in full and submitted to thematic analysis of content. There were 15 in-depth interviews conducted. Results: Variations were identified among the professional groups regarding the previous realization of reports and the understanding of the current systems. The main incentives identified were: patient protection, professional responsibility, professional visibility, severity of errors, post-report feedback, non-punitive and personal approaches. The main barriers to reporting were: attribution of responsibility to another professional, conceptual problems, possibility of internal correction of the error, frustration when making mistakes, fear regarding the unfolding of the error and lack of knowledge of the reporting flows. Conclusions: The study made it possible to understand the factors related to the reporting of drug incidents in the institution where the research was carried out and also made it possible to draw parallels between the perspectives of the professional groups interviewed.